2011
DOI: 10.1128/cvi.05207-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bio-Rad BioPlex Measles, Mumps, Rubella, and Varicella-Zoster Virus IgG Multiplex Bead Immunoassay

Abstract: The goal of this study was to compare the BioPlex 2200 measles, mumps, rubella, and varicella-zoster virus (MMRV) IgG multiplex assays (Bio-Rad Laboratories, Hercules, CA) to routine testing by enzyme immunoassay (EIA). Serum specimens (n ‫؍‬ 500) submitted to our reference laboratory for routine MMRV IgG testing by EIA were also tested by the BioPlex assays. Following testing, the BioPlex measles, mumps, rubella, and varicella-zoster virus assays demonstrated agreements of 91.6% (95% confidence interval [CI],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Serum specimens for all subjects were processed with the BioRad BioPlex 2200 MMRV IgG multiplex flow immunoassay, which has a sensitivity of 92.2% and specificity of 100% for the varicella component when compared to traditional testing via enzyme immunoassay [23], and overall agreement of 96% when compared to anticomplement immunofluorescence tests [24]. Subjects with negative titers received two varicella vaccine doses in accordance with standard immunization practices.…”
Section: Primary Outcomementioning
confidence: 99%
“…Serum specimens for all subjects were processed with the BioRad BioPlex 2200 MMRV IgG multiplex flow immunoassay, which has a sensitivity of 92.2% and specificity of 100% for the varicella component when compared to traditional testing via enzyme immunoassay [23], and overall agreement of 96% when compared to anticomplement immunofluorescence tests [24]. Subjects with negative titers received two varicella vaccine doses in accordance with standard immunization practices.…”
Section: Primary Outcomementioning
confidence: 99%
“…In this study, the correlation of the quantitative result of the BioPlex 2200 MMRV IgG assay and the reference method (PRNT) is higher for "nonequivocal" specimens (Ͼ192 mIU/ml) and specimens with low concentrations of neutralizing antibody do not correlate well. This observation has been previously reported for other EIA methods and is attributed to the fact that PRNT only measures neutralizing IgG, whereas EIA-based tests measure total anti-measles IgG (14,15,20,26,29). This lack of sensitivity may lead to an underestimation of the number of protected individuals in seroepidemiological studies.…”
Section: Discussionmentioning
confidence: 63%
“…Specimens tested on the platform are reported as positive (immune), equivocal, or negative (nonimmune). Previous work has shown that the qualitative results produced by this commercially available assay correlate well with existing EIA methods (20). Because the BioPlex 2200 MMRV IgG assay generates a quantifiable value (relative fluorescence intensity [RFI]), it is possible that this assay can be used as a quantitative method, which is off-label from the commercial product.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…However, some of the international guidelines, while stressing the importance of this value, point out that this cut-off value may vary depending on vaccinations, ethnicity or age [54] . Microarrays: Finally, there are also some serological microarray tests for the simultaneous screening of antibodies against VZV and viruses such as herpes simplex virus (HSV-1 and HSV-2), cytomegalovirus, mumps, rubella or measles [415][416][417][418][419] .…”
Section: Gpelisamentioning
confidence: 99%